Role of Leadership in Organizational Change: A Case Study at Attaqwa Putra Islamic Boarding School Bekasi - Indonesia - Misbah, Muh.; Sulaeman, Suhendar; Bakhri, Syaiful (Asian Journal of Contemporary Education, 2019)
This study aims to find out the leadership role in organizational change at Attaqwa Putra Islamic Boarding School Bekasi Indonesia. The research utilized a case study method. Meanwhile, data collection techniques were through the interview, observation, document analysis, and questionnaire. Analysis data used the reduction system, data display, and verification/conclusions. The results of the research, there are four important leadership roles in organizational change at the Attaqwa Putra Islamic Boarding School Bekasi. First, the Leader as the direction of the direction is reflected in the role of formulating a vision, inspiring subordinates to make changes, and focusing every activity to achieve the school’s vision. Second, leaders as spokespersons are reflected in the role of leaders advising teachers, building relationships with principals through routine coordination meetings, coordinating with teachers through press meetings, and holding support from graduates. Third, leaders as coaches are reflected in the leadership role of building a work team, building trust, encouraging and motivating subordinates, and providing the best service. Fourth, leaders as agents of change are reflected in the role of leadership in deciding to make changes, innovate, anticipate future trends, and determine the direction of boarding school in the future.